University social responsibility: duty or commitment? - Capillo Lucar, Isabel (2020)
The university conceived as a service institution defines University Social Responsibility (RSU) as a management policy, which aims to achieve the ethical quality of its members, through the responsible management of the impacts it generates, and must be assumed with commitment and responsibility contributing to the sustainability of the planet and ensuring a decent life for future generations. In this sense, doubt arises. Is it a duty or commitment?